Surgical Sutures with Porous Sheaths for the Sustained Release of Growth Factors. Issue 23 (5th April 2016) - Li, Jianhua; Linderman, Stephen W.; Zhu, Chunlei; Liu, Hong; Thomopoulos, Stavros; Xia, Younan
Abstract : Surgical sutures with highly porous sheaths are developed using a swelling and freeze‐drying procedure without compromising their mechanical properties. The modified sutures show a high capacity for loading biofactors and are able to release the loaded biofactors in a sustained manner.